Malaysian manufacturers' values in the product design process - Saud, Mohammad Basir; Melan, Mustakim; Adawiyah, Wiwiek Rabiatul (2010)
This study determines the design’s values of the products by Malaysian Small and Medium Industries (SMIs). The triangulation method of research was used in this study. The main data and information were gathered through mailed questionnaires and interviews from managers of Malaysian SMI’s. The findings of this study revealed that Malaysian SMIs are generally using several values such as ergonomics, aesthetics, technical aspects, environmental impacts, value analysis, quality functional deployment, etc for designated products for exports market. It was found that there were differences in “values” in term of priorities when designing or redesigning products for local as compared to foreign customers. Finally, some Malaysian SMIs do not update their knowledge on the availability of tools and techniques in the process of product design.The contribution of study is able to provide a picture of the product design process for developing countries and structuring means for small industrial concerns through improvement product design process.